THE COMPETENCY OF SCHOOL ADMINISTRATORS IN THE DIGITAL AGE EFFECTING THE ACADEMIC AFFAIRS ADMINISTRATION IN PRIMARY SCHOOL UNDER SAKAEO PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Wanngoen, Chatchadaporn; Boonloy, Waiwoot; Nilkote , Reongwit (Journal of MCU Nakhondhat, 2023)
The purposes of the research were to: 1) to study the level of competency of school administrators in the digital age, 2) to study of the academic management level of school administrators in the digital age, 3) to study the relationship between the competencies of school administrators in the digital age that affect academic administration, and 4) to creating a forecasting equation for the performance of school administrators in the digital age that affects academic administration of schools under the sakaeo primary educational service area office 1. It is quantitative research. The sample group includes 313 teachers in schools under the Sa Kaeo Primary Educational Service Area Office, Area 1, academic year 2022, obtained using the proportional stratified random sampling method. The research instrument was a 5-level rating scale, one version, analyzed with statistics, consisting of mean, standard deviation. Pearson’s correlation value and simple regression analysis. The results of the study were as follows: 1) the competency of school administrators in the digital age was at a high level ( = 4.25, S.D. = 0.37), 2) the academic administration of school administrators was at a high level ( = 4.37, S.D. = 0.43), 3) the competencies of school administrators In the digital age, there was a significant high positive relationship with academic administration of schools statistically at the .01 level, and 4) the competencies of school administrators in the digital age affecting management academic work of educational institutions under the sakaeo primary educational service area office 1. The results of the study can create a forecasting equation for the performance of school administrators in the digital era that affects the academic administration of educational institutions under the Sa Kaeo Primary Educational Service Area Office, Area 1. The forecasting equation in the form of raw scores is = 1.630 + 0.601**X and the prediction equation in standard score form is y = 0.701** Zx is in accordance with the set assumptions.